IMPLEMENTASI PERMENDIKBUD RISTEK NO 30 TAHUN 2021 JO PERMENDIKBUD RISTEK NOMOR 55 TAHUN 2024 SEBAGAI PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN SEKSUAL PADA PERGURUAN TINGGI DI KABUPATEN BULELENG - Tegar Bagus Satria; I Wayan Landrawan; Made Sugi Hartono (Jurnal Ilmu Hukum Sui Generis, 2025)
This research aims (1) to find out the implementation of Permendikbud Ristek No. 30 of 2021 in universities in Buleleng Regency as a form of legal protection for victims of sexual violence; (2) to find out the obstacles faced in the implementation of Permendikbud Ristek No. 30 of 2021 in universities in Buleleng Regency; (3) and to find out efforts at universities in Buleleng Regency to overcome challenges and obstacles in the implementation of Permendikbud Ristek No. 30 of 2021. The results showed that (1) The implementation of Permendikbud Ristek No. 30 of 2021 in universities in Buleleng Regency reflects a systematic effort to protect victims of sexual violence, despite the challenges of socialization, patriarchal culture, and lack of facilities, and requires the synergy of all parties so that the policy runs effectively and fairly; (2) Implementation of Permendikbud Ristek No. 30 of 2021 in universities in Buleleng Regency. 30 of 2021 in universities in Buleleng Regency faces obstacles in the form of a lack of understanding of gender, weak reporting mechanisms, lack of victim assistance, and the potential for abuse of academic power, so that legal protection for victims of sexual violence has not been optimal and transparent; (3) Universities in Buleleng Regency are trying to overcome obstacles to the implementation of Permendikbud Ristek No. 30/2021 through periodic counseling, the formation of the PPKS Task Force, and psychological assistance for victims, in order to create an academic environment that is safe, responsive, and in favor of the protection and recovery of victims of sexual violence.